Effect of immediate electrical stimulation in the distal segment of the nerve with Wallerian degeneration in rats with sciatic nerve injury (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Electrical stimulation in the proximal segment is one of the modalities for peripheral nerve injury, although it is prone to cause excessive axonal sprouting growth in the proximal segment of the nerve. This study aimed to show that immediate electrical stimulation in the distal segment of the sciatic nerve in Wistar rats accelerated Wallerian degeneration by increasing the expression of tumor necrosis factor-alpha (TNF-α), interleukin (IL)-10, and galectin-3/MAC-2 macrophages to avoid sprouting axons excessively in the proximal segment. METHODS This was an experimental study using male Wistar rats (Rattus norvegicus) with a randomized post-test only control group design. The treatment group received immediate electrical stimulation (20 Hz, 2 mA, for 5 sec) to the distal nerve after sciatic nerve injury, while the control group received no treatment. After 3 days, tissue samples were extracted from the distal segment of the sciatic nerve to examine the level of TNF-α, IL-10, and galectin 3/Mac-2 macrophages using ELISA and from proximal nerves to histologically examine the sprouting axons. RESULTS Rats in the treatment group had higher TNF-α (52.1 [10.32] versus 40.4 [17.71] pg/100 mg, p = 0.031) and higher IL-10 (918 [167.6] versus 759 [158.9] pg/ml, p = 0.010). Expression of galectin 3/Mac-2 macrophages was similar in both groups (465 [49.5] versus 444 [54.4] pg/100 mg, p = 0.247). The number of sprouting axons was lower in the treatment group (2 [IQR 1–2] versus 2.5 [IQR 2–3], p = 0.003). CONCLUSIONS Immediate electrical stimulation in the distal segment of the sciatic nerve can accelerate nerve regeneration.